Childhood psychological maltreatment and Chinese adolescents' bullying perpetration: a moderated mediation model of angry rumination and empathy - Wang, Xingchao (Journal of family violence, 2024)
Purpose: The current study explored the association between childhood psychological maltreatment and bullying perpetration. Furthermore, it tested a moderated mediation model to examine the role of angry rumination and empathy in this relationship. Methods: A total of 2,286 Chinese adolescents (mean age = 13.46 years, SD = 0.93) completed self-report measures of childhood psychological maltreatment, bullying perpetration, angry rumination, and empathy. SPSS 25.0 was used to evaluate empathy as a moderator of the direct and indirect relationships between childhood psychological maltreatment and adolescents’ bullying perpetration via angry rumination. Results: The findings revealed that adolescents who experienced childhood psychological maltreatment were more likely to bully others, which was mediated by angry rumination. Empathy moderated the relationship between childhood psychological maltreatment and angry rumination and also moderated the relationship between childhood psychological maltreatment and bullying perpetration. Specifically, high empathy enhanced the association between childhood psychological maltreatment and angry rumination, but weakened the association between childhood psychological maltreatment and bullying perpetration. Conclusions: Our study is the first to identify how childhood psychological maltreatment is related to bullying perpetration and the underlying mechanisms, which have important theoretical and practical significance for preventing or intervening in adolescents’ bullying perpetration from family aspects.